Sea ice decline in the Eastern Arctic results in expansion of the freshened surface layer - Rogozhin, Vladimir; Osadchiev, Alexander; Savin, Alexander; Rogozhina, Ekaterina; Georgiev, Anton; Konovalova, Olga (Frontiers in Marine Science, 2025)
In this study, we report an anomalously large freshened surface layer in the Eastern Arctic during ice-free season in 2019. This freshened surface layer is formed by river discharge and sea ice meltwater and is also referred to as the Lena plume, due to the Lena River discharge is its major freshwater source. Based on in situ and satellite data, we demonstrate that in August-September 2019 the Lena plume extended from the Lena Delta in the west to the Wrangel Island in the east, i.e., its zonal extent was approximately 2000 km. The area of the Lena plume varied between 750 000 and 870 000 km2 during this period, which is 1.5 times greater than the assessment of its maximal area in previous years, albeit they were often hindered by the presence of sea ice coverage. The main reasons for this anomalous spreading of the Lena plume are the following. First, intense sea ice melting in the Eastern Arctic in 2019 provided a significantly greater volume of meltwater inflow to the freshened surface layer, as compared to other years. Second, sea ice cleared out of the Laptev and East Siberian seas by the beginning of August and September 2019 respectively, and these seas remained free of ice during for 2 to 3 months (longer ice-free period occurred only in 2007 and 2020). Three months of favorable wind forcing on the Lena plume in July-September 2019 caused its anomalously extensive eastward and northward expansion, together with changes in the vertical structure of the Lena plume. This plume expansion affected the composition of phytoplankton communities, with the intrusion of freshwater species in the eastern part of the East Siberian Sea. The reported expansion of the large Lena plume under favorable sea ice and wind conditions provides the baseline for forecasting the future state of large-scale freshwater cycle in the Arctic Ocean, with an expectedly reduced ice cover.